María Cruz Mina Apat - García-Sanz Marcotegui, Ángel; Osés Gorráiz, Jesús María (Huarte de San Juan. Geografía e Historia, 2014)
María Cruz Mina dedicated more than thirty years of her life to teach and investigate. She contributed notably to the history of Navarra, the topic of her transgressive doctoral thesis, the ideological foundations and evolution of Carlism, the develop of the «fuerismo» and the relationships between the Carlism and Basque nationalism. She also tried compatible citizenship and nationalism, analyzing it from a political point of view in the her opinion the ideal citizenship is the only universal culture nowadays so she suggested recover it and to oppose it the political theology about collective essences.
Keywords: Navarre; carlismo; fuerismo; citizenship; nationalism; human rigth